2015
DOI: 10.1103/physrevb.92.054416
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias effect inAu-Fe3O4dumbbell nanoparticles induced by the charge transfer from gold

Abstract: We have studied the origin of the exchange bias effect in the Au-Fe 3 O 4 dumbbell nanoparticles in two samples with different sizes of the Au seed nanoparticles (4.1 and 2.7 nm) and same size of Fe 3 O 4 nanoparticles (9.8 nm). The magnetization, small-angle neutron scattering, synchrotron x-ray diffraction and scanning transmission electron microscope measurements determined the antiferromagnetic FeO wüstite phase within Fe 3 O 4 nanoparticles, originating at the interface with the Au nanoparticles. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 92 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…This is in contrast with the case of Au/γ-Fe 2 O 3 nanocrystals, in which γ-Fe 2 O 3 has been shown to disfavor such a spin polarization transfer process [94]. A later study of Feygenson et al [38] has indeed confirmed that the charge transfer from the Au nanoparticles is responsible for a partial reduction of the Fe 3 O 4 into the FeO phase at the interface with Au nanoparticles, and that the coupling between the Fe 3 O 4 and FeO induces an EB effect. Since FeO is formed at the interface between Fe 3 O 4 and Au [94], in the case of Au/γ-Fe 2 O 3 core/shell MNPs [93] the absence of FeO suggests that the EB effect is attributed to the presence of γ-Fe 2 O 3 hollow morphology.…”
Section: Exchange Bias Effect In Hybrid Composite Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with the case of Au/γ-Fe 2 O 3 nanocrystals, in which γ-Fe 2 O 3 has been shown to disfavor such a spin polarization transfer process [94]. A later study of Feygenson et al [38] has indeed confirmed that the charge transfer from the Au nanoparticles is responsible for a partial reduction of the Fe 3 O 4 into the FeO phase at the interface with Au nanoparticles, and that the coupling between the Fe 3 O 4 and FeO induces an EB effect. Since FeO is formed at the interface between Fe 3 O 4 and Au [94], in the case of Au/γ-Fe 2 O 3 core/shell MNPs [93] the absence of FeO suggests that the EB effect is attributed to the presence of γ-Fe 2 O 3 hollow morphology.…”
Section: Exchange Bias Effect In Hybrid Composite Nanoparticlesmentioning
confidence: 99%
“…An issue of potential interest is if the surface spin alignment in nanoparticles could be influenced by forming interfaces with other non-magnetic materials [37,38,91,92,93,94,95,96]. If this is indeed possible, then it would provide an excellent mechanism to control the exchange coupling between the surface and core spins in individual MNPs leading to novel magnetic properties.…”
Section: Exchange Bias Effect In Hybrid Composite Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent times, among gold nanocomposites, EB effect has been reported in Au‐Fe 3 O 4 core‐shell and nano‐dumbbell . Presence of FeO phase is quite common for such Au‐Fe 3 O 4 nanomaterials, where the EB arises due to the interface of the antiferromagnetic FeO and ferromagnetic Fe 3 O 4 . This FeO phase is generally obtained as a reduced product of Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%